Are Geopolitical Risks a Permanent Driver of Global Inflation? Evidence from 1985-2024 - Yıldız, Ümit (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).19, 2026)
This study investigates the causal relationship between geopolitical risks and global inflation and examines whether this causal effect, if any, is persistent. To this end, the stationarity of the annual Geopolitical Risk Index (GPR) and global inflation series for the 1985–2024 period was first analyzed using the Lee and Strazicich (2003) two-break unit root test, which concluded that the series are stationary at levels. Subsequently, the data were analyzed using a stationary frequency domain causality approach, revealing a unidirectional causal relationship running from GPR to global inflation at both low and high frequencies. The causality identified at low frequencies indicates that this causal effect is permanent. The findings of the study suggest that mitigating geopolitical risks is of vital importance in the fight against global inflation.